08 Neural correlates of cognition in progressive supranuclear palsy. Issue 3 (15th February 2011) - Ghosh, B C P; Acosta-Cabronero, J; Hodges, J R; Rowe, J B
Abstract : Introduction: Progressive supranuclear palsy (PSP) is characterised by falls, akinesia and supranuclear gaze palsy but cognitive dysfunction is common. We investigated the neural basis of cognitive decline in PSP. Method: 22 PSP patients and 23 matched controls underwent neuropsychological tests including Addenbrookes Cognitive Examination (ACER); MMSE and Frontal Assessment battery (FAB). High-resolution 3T MPRAGE T1-weighted images were acquired and reconstructed, brain-extracted and bias-corrected for voxel-based morphometry (VBM) using SPM5 with total intracranial volume as a nuisance covariate. Results: ACER varied widely among patients but most were impaired on the FAB (20/22 scored ≤15/18) with mean UPDRS-III motor score 34/108 and PSP-rating scale 37. VBM confirmed PSP (vs control) was associated with grey matter atrophy of medial, lateral and orbito-frontal cortex, insula and cerebellum, with white matter atrophy of dorsal midbrain, cerebral peduncles and orbito-frontal region. Lower ACER score was correlated with GM atrophy of medial and lateral prefrontal cortex but not subcortical regions. Conclusions: Patients with PSP are impaired at tests associated with frontal lobe function, but show heterogeneity across other cognitive domains. Variation in global cognition correlates with the degree of frontal cortical atrophy, rather than subcortical volume loss. Further work is required to understand the selective vulnerability of frontal cortex in the subgroup of PSP patients with global cognitive decline.